697 Tumor-targeted CD28 costimulatory bispecific antibodies enhance T cell activation in solid tumors. (9th November 2020) - Hedvat, Michael; Zeng, Veronica; Diaz, Juan; Bonzon, Christine; Avery, Kendra; Rashid, Rumana; Leung, Irene; Bartlow, Norm; Bakhit, Charles; Dragovich, Matthew; Bogart, Liz; Muchhal, Umesh; et al.
Abstract : Background: T cells in the tumor micro-environment require TCR/MHC engagement and co-stimulatory receptor engagement to achieve complete activation. Solid tumors often lack expression of CD28 ligands, so we hypothesized that activation of CD28 signaling could be beneficial in solid tumors. We designed tumor-associated-antigen (TAA) x CD28 bispecific antibodies that conditionally costimulate CD28 only in the presence of TAA and TCR engagement. Clinical application of this class of antibodies has potential to enhance activity of either anti-PD(L)1 antibodies or TAA x CD3 T cell engagers. Methods: We designed a stability and affinity optimized anti-CD28 antibody that can be paired with TAA of choice to engage CD28 monovalently using Xencor's XmAb 2+1 and 1+1 platforms. In vitro T cell activation with these bispecifics was measured by T cell proliferation, cytokine production, and cytotoxicity, in co-cultures of human cancer cell lines mixed with primary human CD3-stimulated T cells. In vitro activity was validated in a CMV recall assay measuring CMV+ T cell proliferation of CMV+ PBMC co-cultured with cancer cell lines ectopically treated with pp65-derived NLV-peptide. In vivo anti-tumor and T cell proliferative activity of B7H3 x CD28 bispecific antibodies were determined in tumor-bearing huPBMC-NSG mice treated simultaneously with TAA x CD3 bispecific antibody. In vivo activity of PDL1 x CD28 antibodies was determined with hCD28 KI mice inoculated with MC38 tumors expressing hPDL1-antigen. Finally, safety and tolerability of B7H3 x CD28 and PDL1 x CD28 was determined in cynomolgus monkeys. Results: B7H3 x CD28 and PDL1 x CD28 antibodies enhanced T cell degranulation, cytokine secretion, and cancer cell cytotoxicity in concert with CD3 stimulation only in the presence of target antigen. B7H3 x CD28, alone or in combination with anti-PD1 antibody, enhanced proliferation of CMV+ T cells recognizing cancer cells loaded with pp65-derived NLV peptide. PDL1 x CD28 also enhanced CMV+ cell expansion but did not synergize with anti-PD1 antibody treatment. B7H3 x CD28 significantly enhanced in vivo anti-tumor activity of TAA x CD3 antibodies while also promoting greater T cell expansion. In hCD28 mice inoculated with MC38 tumors expressing hPDL1, PDL1 x CD28 antibody inhibited tumor growth greater than an anti-PDL1 antibody alone. B7H3 x CD28 and PDL1 x CD28 were well tolerated in cynomolgus monkeys. Conclusions: B7H3 x CD28 and PDL1 x CD28 bispecific antibodies show promising anti-tumor activity and warrant further development.